2022
DOI: 10.1177/20552076221120726
|View full text |Cite
|
Sign up to set email alerts
|

Digitization in health-related self-help – Results of an online survey among self-help organizations in Germany

Abstract: Background Nowadays, much hope and expectations are associated with digitization in the health sector. The digital change also affects health-related self-help. A nationwide survey of self-help organizations (SHOs) aimed to show chances and limitations in the use of interactive IT tools like webforums, online meetings or social media as well as digital infrastructures for their organizational management. In this survey, we also determined whether SHO staff themselves have support and qualification needs with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(37 reference statements)
0
2
0
1
Order By: Relevance
“…Die Befragten, die in einer ambulanten Selbsthilfegruppe waren, gaben mehrheitlich an, dass die Selbsthilfe nicht über ausreichende finanzielle Mittel für die Ausgestaltung der Digitalisierung verfügt. Bereits vor Beginn der Pandemie gaben im Rahmen einer Studie mehr als 70 % der befragten Selbsthilfeorganisationen an, nicht über ausreichende finanzielle Mittel für die Digitalisierung zur Verfügung zu haben [21]. Finanzielle Hilfen für Digitalisierungsmaßnahmen sind daher vor allem für finanziell schwächer aufgestellte Selbsthilfegruppen/ organisationen notwendig.…”
Section: Diskussionunclassified
“…Die Befragten, die in einer ambulanten Selbsthilfegruppe waren, gaben mehrheitlich an, dass die Selbsthilfe nicht über ausreichende finanzielle Mittel für die Ausgestaltung der Digitalisierung verfügt. Bereits vor Beginn der Pandemie gaben im Rahmen einer Studie mehr als 70 % der befragten Selbsthilfeorganisationen an, nicht über ausreichende finanzielle Mittel für die Digitalisierung zur Verfügung zu haben [21]. Finanzielle Hilfen für Digitalisierungsmaßnahmen sind daher vor allem für finanziell schwächer aufgestellte Selbsthilfegruppen/ organisationen notwendig.…”
Section: Diskussionunclassified
“…Before the pandemic, research indicated that the level of digitalization among POs varied widely. While many relied primarily on basic digital communication tools such as websites, email, and social media, others embraced advanced technologies and developed interactive platforms, mobile applications, or electronic patient databases to enhance the use of digital patient data for research [14][15][16]. These differences in digitalization levels may be linked to the organizational characteristics described above, as well as additional factors such as the digital literacy of PO leadership and members and their demographic profile [14].…”
Section: Introductionmentioning
confidence: 99%
“…While many relied primarily on basic digital communication tools such as websites, email, and social media, others embraced advanced technologies and developed interactive platforms, mobile applications, or electronic patient databases to enhance the use of digital patient data for research [14][15][16]. These differences in digitalization levels may be linked to the organizational characteristics described above, as well as additional factors such as the digital literacy of PO leadership and members and their demographic profile [14]. However, despite the significant role of POs as supporters and advocates, we found no comprehensive reviews synthesizing the existing research literature on their digitalization efforts during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%